2022
DOI: 10.1177/15266028221118510
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Selective Intra-arterial Cone-Beam CT Angiography in the Management of Visceral Artery Aneurysms

Abstract: Purpose: The aim of this study is to evaluate the value of selective intra-arterial cone-beam computed tomography angiography (CBCTA) relative to conventional computed tomography angiography (CTA) in understanding visceral artery aneurysm (VAA) morphology, and its impact on treatment planning. Materials and Methods: Between January 2017 and August 2021, all patients who had a diagnosis of VAA and underwent intraoperative CBCTA imaging were retrospectively reviewed. Impact on treatment decisions, optimal C-arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Piron et al [ 25 ] investigated radiation exposure via abdominal CBCT during transarterial chemoembolization (TACE) and reported a DAP of 59.397 (46.290–66.401) Gy⋅cm 2 for a single rotation. Similarly, Berczeli et al [ 3 ] conducted CBCT imaging for visceral aneurysms and found DAP and skin dose values of 57.03 ± 39.67 Gy⋅cm 2 and 223.6 ± 141.3 mGy, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Piron et al [ 25 ] investigated radiation exposure via abdominal CBCT during transarterial chemoembolization (TACE) and reported a DAP of 59.397 (46.290–66.401) Gy⋅cm 2 for a single rotation. Similarly, Berczeli et al [ 3 ] conducted CBCT imaging for visceral aneurysms and found DAP and skin dose values of 57.03 ± 39.67 Gy⋅cm 2 and 223.6 ± 141.3 mGy, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT) is a valuable three-dimensional (3D) volumetric imaging technique widely utilized in neuroradiology and interventional oncology [ 1 , 2 ]. It offers significant advantages in terms of visualizing complex anatomical structures, guiding percutaneous punctures and catheterizations, verifying intracranial stent placement in real time, and promptly monitoring intracranial hemorrhages or infractions [ 3 , 4 , 5 , 6 , 7 , 8 ]. However, a notable drawback of this technique is the additional degree of radiation exposure, especially when multiple CBCT scans are performed [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation